2004
DOI: 10.1136/bmj.38070.450891.fe
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for the development of microalbuminuria and macroalbuminuria in patients with type 1 diabetes: inception cohort study

Abstract: Objective To evaluate baseline predictors for the development of persistent microalbuminuria and macroalbuminuria prospectively in patients with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
289
12
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(342 citation statements)
references
References 31 publications
25
289
12
16
Order By: Relevance
“…Microalbuminuria develops in 30–60% of humans with type I diabetes,21, 22 and commonly precedes the development of overt glomerular disease and proteinuria 23. However, there is a paucity of information regarding urine albumin concentration in dogs with spontaneous DM.…”
Section: Discussionmentioning
confidence: 99%
“…Microalbuminuria develops in 30–60% of humans with type I diabetes,21, 22 and commonly precedes the development of overt glomerular disease and proteinuria 23. However, there is a paucity of information regarding urine albumin concentration in dogs with spontaneous DM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is no doubt that improved glucose control can transform the natural history of type 1 diabetes [11], but the fall in HbA 1 c from 8.9 to 8.5% reported by the Danish study seems modest in relation to the simultaneous 60% reduction in the incidence of nephropathy [6]. Another study from the same centre found that 33.6% of a 1979-1984 inception cohort developed persistent microalbuminuria or proteinuria within 20 years of diabetes onset, implying that the reported delay in progression to nephropathy in this group is attributable to secondary prevention in those with incipient, but established, disease [12]. This raises the concern that the burden of nephropathy may have been postponed rather than prevented.…”
mentioning
confidence: 78%
“…Compared with normoalbuminuric patients, patients with persistent microalbuminuria have threefold to fourfold greater risk of progression to proteinuria and ESRD. Current studies indicate that between 20% and 45% of microalbuminuric type 1 diabetic patients will progress to proteinuria after about 10 years of follow-up, whereas 20% to 25% will return to normoalbuminuric levels (Hovind P, 2004) and the rest will remain microalbuminuric. At this stage, glomerular lesions are generally more severe than in the previous stages, and blood pressure tends to be increasing, often into the hypertensive range.…”
Section: Diabetic Glomerulopathy 333mentioning
confidence: 99%